2008
DOI: 10.1002/pola.22656
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted ring‐opening polymerization of p‐dioxanone

Abstract: The ring-opening polymerization (ROP) of p-dioxanone (PDO) under microwave irradiation with triethylaluminum (AlEt 3) or tin powder as catalyst was investigated. When the ROP of PDO was catalyzed by AlEt 3 , the viscosity-average molecular weight (M v) of poly(p-dioxanone) (PPDO) reached 317,000 g mol À1 only in 30 min, and the yield of PPDO achieved 96.0% at 80 8C. Tin powder was successfully used as catalyst for synthesizing PPDO by microwave heating, and PPDO with M v of 106,000 g mol À1 was obtained at 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Microwave irradiation has a number of advantages over conventional heating, such as its noncontacting, instantaneous, rapid, and high specific heating nature 11. Recently, our results showed that compared with that of PPDO synthesized under traditional heating, PPDO with a relatively high viscosity‐average molecular weight ( M v ) and yield could be obtained under microwave irradiation 12. Yoo et al13 prepared polycarbonate/MMT nanocomposites by microwave‐aided solid‐state polymerization, and found that microwave solid‐state polymerized nanocomposite showed an exfoliated and/or intercalated structure, whereas conventional solid‐state polymerization with oil heating only increased the gallery size of the MMT.…”
Section: Introductionmentioning
confidence: 82%
“…Microwave irradiation has a number of advantages over conventional heating, such as its noncontacting, instantaneous, rapid, and high specific heating nature 11. Recently, our results showed that compared with that of PPDO synthesized under traditional heating, PPDO with a relatively high viscosity‐average molecular weight ( M v ) and yield could be obtained under microwave irradiation 12. Yoo et al13 prepared polycarbonate/MMT nanocomposites by microwave‐aided solid‐state polymerization, and found that microwave solid‐state polymerized nanocomposite showed an exfoliated and/or intercalated structure, whereas conventional solid‐state polymerization with oil heating only increased the gallery size of the MMT.…”
Section: Introductionmentioning
confidence: 82%
“…As far as the DS was concerned, it was almost changeless in the practical time reaction scale from 60 to 180 min. The results indicated that, in the latter period of the reaction, the prolongation of reaction time made the new generating side-chains shorter and the promotion of DS more slow, owing to some side reaction such as the chain-transferring reaction and the inter-molecular or intra-molecular transesterification (Chen et al, 2008). Fig.…”
Section: Analysis Of the Reactivity Of The Graft Polymerizationmentioning
confidence: 97%
“…[125] Comparison experiments with CH revealed the superiority of the microwave-assisted protocol for the metal-catalyzed polymerization in terms of molecular weights and yields. The acceleration of the polymerization of lactic acid under microwave irradiation in a single-mode CEM Discover microwave reactor was reported by Takeuchi and coworkers.…”
Section: Cyclic Estersmentioning
confidence: 98%